PENGUJIAN IN VITRO XILOOLIGOSAKARIDA SEBAGAI KANDIDAT PREBIOTIK - Asnia Zainuddin; Eddy Bagus Wasito; Ni Nyoman Tri Puspaningsih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
The objectives of this study were to fi nd the in-vitro effect of xyloolygosaccharide on the cell count of Lactobacillus casei Shirota strain, to identify the effect of xyloolygosaccharide on the production of lactic, acetic, propionic and butyric acid (short chain fatty acid = SCFA), and to prove the effect of xyloolygosaccharide on the change of pH value.This was a laboratory experimental study using complete randomized design with 4 treatments, i.e, MRS broth media added xyloolygosaccharide with concentrations of 0% (control), 1%, 3%, and 5%, which were then inoculated with Lactobacillus casei Shirota strain and incubated for 6,12, 18, and 24 hours. The Lactobacillus casei Shirota strain cell count was counted using Drop plate. Data obtained were analyzed statistically using two way ANOVA with signifi cance level of 5%. The type and level of organic acids, i.e., lactic, acetic, propionic, and butyric acids (SCFA), formed in incubation time of 12 hours, were measured using gas chromatography and the change of pH value during incubation time was measured using pH paper. Results showed that xyloolygosaccharide addition MRS Broth media provided highly signifi cant interaction effect on the cell count of Lactobacillus casei Shirota strain (p<0.05). The result of gas chromatography showed that the addition of xyloolygosaccharide in MRS Broth media could increase Lactobacillus casei Shirota strain metabolism activity that produced lactic, acetic, propionic, and butyric acid. The reduction of pH value showed that the lowest pH value of 3.8 after the addition of 5% xyloolygosaccharide with incubation time of 24 hours. In conclusion, the addition of xyloolygosaccharide with concentrations of 1%, 3%, and 5% in MRS Broth media with incubation periods of 6, 12, 18, and 24 hours can increase Lactobacillus casei Shirota strain cell count, increase the metabolism activity of Lactobacillus casei Shirota strain, capable in producing SCFA in incubation time of 12 hours, and results in the reduction of pH value.